Spigelian Hernia in a 14-Year-Old Girl: A Case Report and Review of the Literature - Claudio Spinelli; Silvia Strambi; Valentina Pucci; Josephine Liserre; Giacomo Spinelli; Carlo Palombo (Georg Thieme Verlag KG, 2014)
Abstract Spigelian hernia (SH) is a surgical rarity in children, which occurs through slit-like defects in the anterior abdominal wall adjacent to the semilunar line, the convexity lateral line which joins the nine ribs to the pubic tubercle and signs the limit between the muscular and aponeurotic portion of transversus abdominis muscle. As there are no specific symptoms and signs, the diagnosis is difficult, especially in children. We report a case of SH that comes to our observation: a 14-year-old girl presented recurrent abdominal pain associated to intermittent palpable mass in the paraumbilical region. Starting from our case report, we review the literature of pediatric SH from 2000 to 2013 and we describe the anatomy, etiology, clinical presentation, instrumental diagnosis, and surgical technique of pediatric SH.